2010
DOI: 10.1016/j.clay.2010.06.023
|View full text |Cite
|
Sign up to set email alerts
|

Thermal properties of sodium-exchanged palabora vermiculite

Abstract: Palabora represents an interstratified vermiculite-biotite containing less than 50% vermiculite. The sodium-exchanged form was prepared by immersion in saturated brine at ambient conditions. The sodium content reached the equilibrium level within the first month of exposure. However, XRD spectra continued to evolve and sharpen over a six month period. The thermal-activated exfoliation was studied using thermo-mechanical analysis. The expansion of the neat "vermiculite" commenced at temperatures above 420 C. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
36
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 63 publications
(42 citation statements)
references
References 28 publications
4
36
0
2
Order By: Relevance
“…Selected metal-urea complexes were prepared in a closed 500 mL vessel under constant agitation (200 rpm in an orbital shaker) for 2 h. The metal chloride to urea molar ratio was set at 1:6. vermiculite was added and the ion exchange reaction (between the cationic complex and the interlayer cation) was allowed to proceed for 15 days, based on the slow rate of exchange previously observed (Inoue, 1984;Kodama and Komarncni, 1999;Muiambo et al, 2010;Skipper et al, 1991). The complexes, in the reaction mixture, amounted to 150% CEC.…”
Section: Preparation Of Metal-urea Vermiculitesmentioning
confidence: 99%
See 3 more Smart Citations
“…Selected metal-urea complexes were prepared in a closed 500 mL vessel under constant agitation (200 rpm in an orbital shaker) for 2 h. The metal chloride to urea molar ratio was set at 1:6. vermiculite was added and the ion exchange reaction (between the cationic complex and the interlayer cation) was allowed to proceed for 15 days, based on the slow rate of exchange previously observed (Inoue, 1984;Kodama and Komarncni, 1999;Muiambo et al, 2010;Skipper et al, 1991). The complexes, in the reaction mixture, amounted to 150% CEC.…”
Section: Preparation Of Metal-urea Vermiculitesmentioning
confidence: 99%
“…Thermomechanical analysis of neat and sodium-exchanged vermiculite revealed that the expansion behaviour varied considerably from flake to flake (Muiambo et al, 2010). Hillier et al (2013) recently offered a plausible and convincing mechanism for the thermal exfoliation of vermiculite.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In intumescent fire barriers applications it is desirable that the vermiculite exfoliates at relatively lower temperatures [11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%